THE ROLE OF EMPOWERMENT OF THE COOPERATIVE AND MSME OFFICE IN THE DEVELOPMENT OF SMALL AND MEDIUM MICRO ENTERPRISES IN MEDAN CITY - Annisa Edelia; Nuri Aslami (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
Medan City Small and Medium Enterprises (SMEs) development still faces several obstacles such as capital, marketing, the use of technology, human resource capabilities, and business licensing. Based on the background of the research, the purpose of this study is; analyzing the empowerment provided by Medan City SMEs to SMEs in Medan; analyzing the development of SMEs in Medan City that have received empowerment from Medan City Cooperatives Service and SMEs; The research method used is qualitative with descriptive. The results showed that the role of Medan City Cooperatives and SMEs office has been able to increase the development of SMEs in Medan City in terms of improving product quality, product diversification, production amount, and business profits. The development occurred mainly due to the empowerment of product marketing and ease of licensing. However, there are some drawbacks in the empowerment of technology utilization and empowerment of HR capabilities in the form of training programs that have not run optimally and evenly. Capital empowerment is also still lacking because the capital of equipment assistance has not been fully able to overcome the constraints of capital funding in SMEs.